2019
DOI: 10.5334/aogh.2093
|View full text |Cite
|
Sign up to set email alerts
|

Breastfeeding Knowledge and Behavior Among Women Visiting a Tertiary Care Center in India: A Cross-Sectional Survey

Abstract: Background: Breastfeeding is commonly practiced by a majority of mothers in developing countries, though there are widespread misconceptions about optimal breastfeeding traditions. In addition to culturally prominent rituals and social norms, incorrect and inadequate breastfeeding knowledge is major factors for this high-risk behavior. Objectives: To assess knowledge, attitude and practices of breastfeeding among girls and women visiting a tertiary care center in India … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
42
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(53 citation statements)
references
References 21 publications
8
42
0
3
Order By: Relevance
“…Studies from various parts of India have reported different rates of pre lacteal feeds viz 4.3%, 27%, 32.03%, 50.81%. [ 14 22 23 24 ] In our study, the rate of pre lacteal feeds was 65.1%. Family customs and pressure from relatives might be the possible reasons for giving pre lacteal feeds.…”
Section: Discussionmentioning
confidence: 47%
See 1 more Smart Citation
“…Studies from various parts of India have reported different rates of pre lacteal feeds viz 4.3%, 27%, 32.03%, 50.81%. [ 14 22 23 24 ] In our study, the rate of pre lacteal feeds was 65.1%. Family customs and pressure from relatives might be the possible reasons for giving pre lacteal feeds.…”
Section: Discussionmentioning
confidence: 47%
“…[ 13 ] Almost all the mothers 98.3% believed that breast feeding boosts mother and child bonding. This is large number as compared to the findings of studies conducted by Priya Sultania et al (71%)[ 14 ] and Eman S Mohd et al (78.6%). [ 15 ] Colostrum was given to 60.7% babies which is less than that reported by studies done in Madhya Pradesh (82%) and Varanasi (90%).…”
Section: Discussionmentioning
confidence: 65%
“…The questionnaire was developed by the researchers to explore predictors of exclusive breastfeeding and participants’ knowledge about it. The items were adapted from recent standardized inventories exploring breastfeeding knowledge and attitudes in the Middle Eastern,[12] Asian,[13] and African regions. [14] It was adapted further by senior neonatologists, pediatricians, family physicians, and public health research experts.…”
Section: Methodsmentioning
confidence: 99%
“…Rahalkar et al and Sultania et al reported that only 50.6% and 45% babies were breastfed within an hour respectively. 12,15 A predominant majority of mothers (91%) knew that breastfeeding should be continued for 2 years and 105 (72.9%) intended to breastfeed up to 24 months. These findings were consistent with study by Chaudhary et al that found 75% mothers were aware that they should continue breastfeeding till the age of 2 years.…”
Section: Resultsmentioning
confidence: 99%